Intermedial Maps: The Street as Site of Cultural-Political Regulation in Modern Brazil - Read, Justin (Intermédialités / Intermediality, 2009)
Since the late 19th century Rio de Janeiro has grown in relation to two primary spatial axes: the planned and regularized cidade (“city”) where most wealth and power are located; and the unregulated morro (“hill”) where most poverty has been concentrated. The history of social order in modern Brazil may not flow from the city per se, but rather from the streets that link cidade and morro the spaces that channel movement between regulated and unregulated areas of the city. One might argue that the modernization of Brazil since 1900 has followed the mapping of Rio de Janeiro’s streets over the same period. Such a claim would require a kind of “alternate” or “intermedial” cartography in which various media are employed to evoke a wide range of sensorial impressions of the city’s streets. This essay therefore attempts an intermedial mapping of Rio’s streets through readings of modernist poetry, modernist architecture, and post-modern television.